Wind tunnel studies of pressure distribution around a 5:1 rectangular cylinder - Nguyen, Dinh Tung; Owen, John; Hargreaves, David (2016)
In this paper, a wind tunnel study is described focusing on analysing the pressure distribution and correlation around both static and dynamic 5:1 rectangular cylinders in smooth and turbulent flow. Results from the static tests highlighted the significant influences of the turbulence on the surface pressure distribution. For the dynamic section, the VIV was triggered by the motion-induced leading edge vortex; a strongly correlated flow feature close to the trailing edge was found to be responsible for an increase in the amplitude of the vortex-induced vibration. An increase in the turbulence effectively weakened the motion-induced leading edge vortex or removed the flow feature close to the trailing edge, which led to a large reduction in the VIV response.